2020
DOI: 10.1016/j.cam.2019.112502
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel interpolation of nonuniform samples with application to image recovery

Abstract: The multichannel trigonometric reconstruction from uniform samples was proposed recently. It not only makes use of multichannel information about the signal but is also capable to generate various kinds of interpolation formulas according to the types and amounts of the collected samples. The paper presents the theory of multichannel interpolation from nonuniform samples. Two distinct models of nonuniform sampling patterns are considered, namely recurrent and generic nonuniform sampling. Each model involves tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Part 1: Feature extraction using only the original image, without feature smoothing and highlighting. Part 2: Replacement of the original Gaussian filtering and equalization histogram with median filtering [30] (smoothed) and the Laplace operator [31] (highlighted). The reason for choosing these two filtering operations is because It is also a common smoothing and highlight filtering image, which has representative.…”
Section: ) Structural Properties and Algorithm Independencementioning
confidence: 99%
“…Part 1: Feature extraction using only the original image, without feature smoothing and highlighting. Part 2: Replacement of the original Gaussian filtering and equalization histogram with median filtering [30] (smoothed) and the Laplace operator [31] (highlighted). The reason for choosing these two filtering operations is because It is also a common smoothing and highlight filtering image, which has representative.…”
Section: ) Structural Properties and Algorithm Independencementioning
confidence: 99%
“…Part 1 is feature extraction using only the original image, without feature smoothing and highlighting. Part 2 is the replacement of the original Gaussian filtering and equalization histogram with median filtering [51] (smoothed) and the Laplace operator [52] (highlighted). The reason for choosing these two filtering operations is because it is also a common smoothing and highlighted filtering image.…”
Section: Structural Properties and Algorithm Independencementioning
confidence: 99%
“…The classical multichannel sampling theorem [1] is only available for the bandlimited functions in the sense of Fourier transform and it has been generalized for the bandlimited functions in the sense of fractional Fourier transform (FrFT) [4], linear canonical transform (LCT) [5,6] and offset LCT [7]. In a real application, only finitely many samples, albeit with large amount, are given in a bounded region [8]. That is, the underlying signal is time-limited.…”
Section: Introductionmentioning
confidence: 99%
“…And the matrix involved in this inverse problem may have a large condition number if the sample sets {g m ( 2πp L ), 0 ≤ p ≤ L − 1}, 1 ≤ m ≤ M have a high degree of relevance. In spite of this, in [8,12], the authors showed that the large scale (N s ) inverse problem could be converted to a simple inversion problem of small matrices (M × M ) by partitioning the frequency band into small pieces. Moreover, the closed-form of the MCI formula as well as the FFT-based implementation algorithm (see Algorithm 1) were provided.…”
Section: Introductionmentioning
confidence: 99%